Unemployment Benefits, Active Labor Market Policies, and Labor Market Outcomes : Evidence from New Global Data - Ulku, Hulya (World Bank, Washington, DC, 2022)
Using novel data on unemployment benefits and active labor market policies in 191 countries in 2019 and 2020, this paper investigates the patterns of unemployment benefits and active labor market policies and their relationship with labor market outcomes. This study is unique in that it covers a large number of developing as well as developed countries and examines the association of both unemployment benefits and active labor market policies with several labor market outcomes at different income levels. According to new data, in the first half of 2020, about 48 percent of countries had an unemployment benefit scheme compared to 82 percent that had some form of active labor market policy. The econometric analyses show that productivity growth has a positive relationship with both unemployment benefits and active labor market policies in upper-middle-income countries and with active labor market policies in low- and lower-middle-income countries, but a negative relationship with both unemployment benefits and active labor market policies in high-income countries. The findings also indicate a consistent negative association of active labor market policies with the rate of self-employment in all income groups and a negative association with the rate of employment in upper middle-income countries. These findings provide new insights on the patterns of unemployment benefits and active labor market policies and their interlinkages with labor market policies at different income levels.